2023
DOI: 10.3390/en16041990
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Procedure for Measuring the Electrical Resistance of Fastening Systems in Urban Railway Tracks

Abstract: Electrical resistance is among the characteristics that fastening systems must meet to ensure the proper functioning of signaling systems in railway infrastructure. The EN 13146-5:2012 standard specifies a laboratory testing method for determining the electrical resistance under wet conditions between running rails provided by a fastening system on steel or concrete sleepers. In urban railway tracks, the electrical resistance of fastening systems affects the stray current; however, there is no standardized ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the laboratory measurements of the electrical resistance of the fastening system on a concrete base, the electrical resistance was more than 3 × 10 3 kΩ [50]. Based on the results presented in [49], it can be concluded that in order to prevent stray currents, it is necessary that the metallic components of the fastening systems are not in direct contact with the rail, to prevent current leakage through the fasteners into the track base. This can be achieved by the use of insulating pads between the rail and the clip or by preventing contact between the fastening system components and the track base, i.e., by insulating the anchor bolts in indirect fastening systems like in the Zagreb 21 CTT fastening system.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…In the laboratory measurements of the electrical resistance of the fastening system on a concrete base, the electrical resistance was more than 3 × 10 3 kΩ [50]. Based on the results presented in [49], it can be concluded that in order to prevent stray currents, it is necessary that the metallic components of the fastening systems are not in direct contact with the rail, to prevent current leakage through the fasteners into the track base. This can be achieved by the use of insulating pads between the rail and the clip or by preventing contact between the fastening system components and the track base, i.e., by insulating the anchor bolts in indirect fastening systems like in the Zagreb 21 CTT fastening system.…”
mentioning
confidence: 95%
“…When effective drainage is provided in tracks with discretely fastened rails and the rails are not in contact with the electrolyte, each fastening system provides a spot resistance to ground [48], so by using the appropriate type of the fastening system, R tg values can be increased. The electrical resistance of five different types of fastening systems on concrete base is analyzed in paper [49]. The results show that the electrical resistance of indirect fastening systems is significantly higher than resistance of direct systems, with an incomparably higher electrical resistance value found in the sample of continuously fastened rail (Figure 5).…”
mentioning
confidence: 99%
See 2 more Smart Citations